(untitled) (CIPEEX, 2025)
INTRODUCTION: Systemic lupus erythematosus (SLE) is a chronic, inflammatory, multisystemic autoimmune disease. Treatment involves different classes of drugs, which are essential for disease control but may also cause adverse effects that can worsen the clinical condition and impair patients’ quality of life. OBJECTIVE: To characterize variables related to the pharmacological profile and adverse effects in patients with SLE during August 2025. METHODS: This was a cross-sectional, descriptive, and observational study with a quantitative approach. Data collection was based on an online questionnaire via Google Forms answered by patients with SLE during August 2025. RESULTS: A total of 34 participants were included in the study; of these, 76.47% (26/34) used corticosteroids, and among them, 88.46% (23/26) also used other drugs, such as hydroxychloroquine (73.91%; 17/23) and immunosuppressants (30.43%; 7/23). The most frequently reported corticosteroid-related adverse effects were weight gain (84.8%; 22/26) and mood changes (75.8%; 19/26). Hydroxychloroquine was used by 91.17% (31/34) of patients. Among these, 64.51% (20/31) combined it with other drugs, mainly immunosuppressants (60%; 12/20) and corticosteroids (20%; 4/20). Reported hydroxychloroquine-related adverse effects included muscle weakness or pain (45.2%; 14/31) and gastrointestinal problems (41.9%; 13/31). All participants reported regular follow-up with healthcare professionals, most commonly rheumatologists (67.64%; 23/34), while 32.35% (11/34) were followed by other professionals. In addition to the diagnosis of SLE, 55.9% (18/34) reported comorbidities, mainly hypertension (50%; 9/18) and cardiovascular diseases (22.2%; 4/18). CONCLUSIONS: The results show that the pharmacological management of patients with SLE predominantly involves the use of corticosteroids and hydroxychloroquine, often in combination with immunosuppressants. Despite therapeutic effectiveness, a high frequency of adverse effects was observed, especially those related to corticosteroids (weight gain and mood changes) and hydroxychloroquine (musculoskeletal and gastrointestinal symptoms). Furthermore, the presence of comorbidities highlights the clinical complexity of these patients, who require multidisciplinary follow-up. Therefore, continuous monitoring of adverse effects and individualized therapy are essential to optimize quality of life and reduce treatment-related complications in SLE.